I Can Read! Marley : The Dog Who Cried Woof - Hill, Susan, 1942-; Grogan, John 1957-; Halverson, Lydia (New York : Harper, 2011)
Marley barks all day long, but when something important happens, he is worried his family will not pay attention to his warning.
Keywords: Dogs -- Fiction; Animal sounds -- Fiction